Identifying the sources, spatial distributions, and pollution status of heavy metals in soils from the southern coast of Laizhou Bay, eastern China. Issue 8 (17th November 2019) - Lv, Jianshu; Xia, Qing; Yan, Tang; Zhang, Manlin; Wang, Zheng; Zhu, Linyu
ABSTRACT: This study identified the spatial distributions, the sources, and the ecological risks of eight heavy metals in the southern coast of Laizhou Bay, eastern China. For this purpose, a total of 111 topsoil (0∼20 cm) samples were collected from, and analyzed for eight heavy metals (Co, Cr, Cu, Hg, Mn, Ni, Pb, and Zn). The average concentrations of Cr, Cu, Hg, Mn, Ni, and Zn were higher than the background values of soils originating from coastal sediment in Shandong Province, indicating the obvious accumulations of these heavy metals in surface soils. Co, Cr, Mn, and Ni mainly came from the parent material, while Cu, Pb, and Zn were affected by both natural sources and human activities. Hg mainly originated from the atmospheric deposition of emissions from coal combustion and the chemical industry. The areas with high contents of heavy metals were consistent with the locations of industrial sites. The geoaccumulation indices and potential ecological risk indices for the heavy metals showed that only a few samples were moderately or strongly polluted by Cu, Pb, Ni, and Zn. However, Hg in the eastern part was at the strong and extreme ecological risk levels, which should receive attention.